Interaction of the electron density fluctuations with electron cyclotron waves from the equatorial launcher in ITER. (2nd November 2017) - Snicker, A; Poli, E; Maj, O; Guidi, L; Köhn, A; Weber, H; Conway, G D; Henderson, M; Saibene, G
Abstract: We present a numerical investigation of electron cyclotron beams interacting with electron density fluctuations in the ITER 15 MA H-mode scenario. In particular, here we study how the beam from the equatorial launcher, which shall be utilized to influence the sawtooth instability, is affected by the fluctuations. Moreover, we present the theory and first estimates of the power that is scattered from the injected O-mode to a secondary X-mode in the presence of the fluctuations. It is shown that for ITER parameters the scattered power stays within acceptable limits and broadening of the equatorial beams is less than those from the upper launcher.